Associations between prenatal exposure to cadmium and lead with neural tube defect risks are modified by single-nucleotide polymorphisms of fetal MTHFR and SOD2: a case-control study - Mengyuan Liu; Jinhui Yu; Zaiming Su; Ying Sun; Yaqiong Liu; Qing Xie; Zhiwen Li; Linlin Wang; Jie Zhang; Lei Jin; Aiguo Ren (BMC, 2021)
Abstract Background Prenatal exposure to heavy metals is implicated in the etiology of birth defects. We investigated whether concentrations of cadmium (Cd) and lead (Pb) in umbilical cord tissue are associated with risk for neural tube defects (NTDs) and whether selected genetic variants of the fetus modify their associations. Methods This study included 166 cases of NTD fetuses/newborns and 166 newborns without congenital malformations. Umbilical cord tissue was collected at birth or elective pregnancy termination. Cd and Pb concentrations were assessed by inductively coupled plasma-mass spectrometry, and 20 single-nucleotide polymorphisms (SNPs) in 9 genes were genotyped. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to estimate the risk for NTDs in association with metal concentrations or genotype using logistic regression. Multiplicative-scale interactions between the metals and genotypes on NTD risk were assessed with logistic regression, and additive-scale interactions were estimated with a non-linear mixed effects model. Results Higher concentrations of Cd were observed in the NTD group than in the control group, but no difference was found for Pb. Concentrations of Cd above the median level showed a risk effect, while the association between Pb and NTD risk was not significant in univariate analyses. The association of Cd was attenuated after adjusting for periconceptional folic acid supplementation. Fetuses with the AG and GG genotypes of rs4880 in SOD2 (superoxide dismutase 2) tended to have a lower risk, but fetuses with the CT and TT genotypes of rs1801133 in MTHFR (5,10-methylenetetrahydrofolatereductase) have a higher risk for NTDs when compared to their respective wild-type. rs4880 and Cd exhibited a multiplicative-scale interaction on NTD risk: the association between higher Cd and the risk for NTDs was increased by over fourfold in fetuses carrying the G allele [OR 4.43 (1.30-15.07)] compared to fetuses with the wild-type genotype. rs1801133 and Cd exposure showed an additive interaction, with a significant relative excess risk of interaction [RERI 0.64 (0.02-1.25)]. Conclusions Prenatal exposure to Cd may be a risk factor for NTDs, and the risk effect may be enhanced in fetuses who carry the G allele of rs4880 in SOD2 and T allele of rs1801133 in MTHFR.